Parent's Knowledge About The Impact of Television and Gawn Exposure on Sexual Behavior In Children 4-6 Years Old in Wolo Village, Penawangan District, Grobogan District - Andareza, Marta Dina; Pranoto, Yuli Kurniawati Sugiyo (BELIA: Early Childhood Education Papers, 2021)
This study aims to: (1) describe how parental knowledge about the impact of exposure to television use and devices on sexual behavior of children aged 4-6 years (2) to analyze the factors that influence parental knowledge about the impact of exposure to television use and gadgets on sexual behavior children aged 4-6 years (3) analyze parental strategies in minimizing the impact of exposure to television use and devices on sexual behavior of children aged 4-6 years. The approach in this research is descriptive qualitative. Informants in this study were parents of children aged 4-6 years.The results of this study are: (1) parents with a junior high school education level consider that preschool children cannot be negatively impacted by the use of gadgets and television, parents with high school education level say they know that television and mobile devices can affect children's sexual behavior, parents with educational level S1 said that broadcasts on television and devices affect sexual behavior of children. (2) The factors that influence parental knowledge about the impact of exposure to the use of television and devices on sexual behavior in children 4-6 years are factors of parental education level, parent's occupation. (3) The strategy of parents to minimize the impact of exposure to television use and devices on sexual behavior in children is by implementing time restrictions,